A rare case of severe right heart failure due to pulmonary artery lymphomatoid granulomatosis. (10th September 2020) - Su, Hongling; Wei, Rong; Duan, Yichao; Guo, Zhaoxia; Wang, Aqian; Jiang, Na; Li, Wanpeng; Zhu, Yan; Guo, Yanqing; Zhang, Min; Zhang, Yan; Cao, Yunshan
Abstract: Lymphomatoid granulomatosis is a rare, vascular‐centric, and vessel‐destroying lymphoproliferative disease that hardly involves the pulmonary arteries. Herein, we report a case with severe right heart failure and pulmonary arterial stenosis caused by pulmonary artery lymphomatoid granulomatosis. This case was diagnosed by percutaneous transluminal pulmonary artery biopsy and was effectively treated with stent implantation and steroid administration.